Yeosuana marina sp. nov., isolated from shallow-sea hydrothermal systems off Kueishantao Island. Issue 12 (19th December 2020) - Zhang, Qingfeng; Lin, Dan; Ye, Jianing; Lin, Ta-Hui; Li, Chenlan; Lin, Huaying; Sun, Xueqiong; Tang, Kai
Abstract : A novel Gram-stain-negative, non-flagellated, non-motile, rod-shaped (0.4–0.6×1.8–2.5 µm), aerobic bacterial strain, designated JLT21 T, was isolated from seawater of a shallow-sea hydrothermal system. Growth occurred with 0–4.0 % (w/v) NaCl (optimum, 2.0 % NaCl), at 8–45 °C (optimum, 25 °C) and at pH 3.0–10.0 (optimum, pH 7.0). Analysis of 16S rRNA gene sequences revealed that strain JLT21 T showed the highest 16S rRNA gene sequence similarity to Gaetbulibacter aquiaggeris KEM-8 T (97.2 %), Gaetbulibacter marinus IMCC1914 T (96.9 %) and Yeosuana aromativorans GW1-1 T (96.9 %). Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain JLT21 T clustered with Y. aromativorans GW1-1 T . The predominant respiratory quinone of strain JLT21 T was menaquinone-6 (MK-6). Polar lipids were phosphatidylcholine, phosphatidylglycerol, phosphatidylethanolamine, three unidentified glycolipids and four unidentified lipids. The major fatty acids of strain JLT21 T were iso-C15 : 0 (21.7 %), C16 : 1  ω 6 c / ω 7 c (11.5 %) and iso-C17 : 0 3-OH (10.9 %). The DNA G+C content of strain JLT21 T was 32.6 %. On the basis of polyphasic analysis, strain JLT21 T is considered to represent a novel species of the genus Yeosuana, for which the name Yeosuana marina sp. nov. is proposed. The type strain of Yeosuana marina is JLT21 T (=CGMCC 1.15787 T =JCM 31511 T ). The study helps us better understand the bacterial species in the shallow-sea hydrothermal system and their adaptations to the hydrothermal environment.